NBEA gene variant in a child with developmental disorder and epilepsy: a case report - Huang, Xiaoli; Wu, Wen-Lin; Song, Jingjing; Tian, Yang; Zhou, Yilan; Wei, Shitao; Yu, Bin; Qin, Luoxiao; Yang, Sida (Frontiers in Neuroscience, 2025)
The NBEA gene encodes Neurobeachin, a brain-specific kinase-anchoring protein that plays a critical role in vesicle trafficking and synaptic regulation. Pathogenic variants in NBEA are definitively associated with neurodevelopmental disorders accompanied by epilepsy, including intellectual disability, autism spectrum disorder, and myoclonic-astatic epilepsy–like phenotypes. Most reported disease-causing variants are de novo loss-of-function mutations, and although genotype–phenotype correlations remain limited, early-onset generalized seizures are frequently observed. Here, we describe a Chinese child presenting with global developmental delay and recurrent seizures with febrile sensitivity. Brain magnetic resonance imaging revealed no structural abnormalities, while electroencephalography showed epileptiform abnormalities. Genetic analysis identified a de novo nonsense variant in the NBEA gene: c.4715C > A [p.(Ser1572Ter)]. According to the American College of Medical Genetics and Genomics guidelines, the variant was classified as pathogenic. NBEA mutations are associated with neurodevelopmental disorders with or without early-onset epilepsy. Although no additional pathogenic variants were identified in the exome, the influence of other undetected genetic or epigenetic modifiers on the observed phenotype cannot be excluded. This case therefore refines the phenotypic spectrum of NBEA-related disorders, emphasizing that the c.4715C > A [p.(Ser1572Ter)] variant may be associated with developmental impairment and epilepsy with possible febrile sensitivity.